Structural and Biochemical Consequences of Disease-Causing Mutations in the Ankyrin Repeat Domain of the Human TRPV4 Channel - Inada, Hitoshi (American Chemical Society, 2012)
[Image: see text] The TRPV4 calcium-permeable cation channel plays important physiological roles in osmosensation, mechanosensation, cell barrier formation, and bone homeostasis. Recent studies reported that mutations in TRPV4, including some in its ankyrin repeat domain (ARD), are associated with human inherited diseases, including neuropathies and skeletal dysplasias, probably because of the increased constitutive activity of the channel. TRPV4 activity is regulated by the binding of calmodulin and small molecules such as ATP to the ARD at its cytoplasmic N-terminus. We determined structures of ATP-free and -bound forms of human TRPV4-ARD and compared them with available TRPV-ARD structures. The third inter-repeat loop region (Finger 3 loop) is flexible and may act as a switch to regulate channel activity. Comparisons of TRPV-ARD structures also suggest an evolutionary link between ARD structure and ATP binding ability. Thermal stability analyses and molecular dynamics simulations suggest that ATP increases stability in TRPV-ARDs that can bind ATP. Biochemical analyses of a large panel of TRPV4-ARD mutations associated with human inherited diseases showed that some impaired thermal stability while others weakened ATP binding ability, suggesting molecular mechanisms for the diseases.